2018
DOI: 10.18520/cs/v115/i10/1928-1937
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of <i>in Vitro</i> and <i>in silico</i> Anti-Hyperglycaemic Action of Bioflavonoids Isolated from Different Citrus Peels

Abstract: In this study, flavonoid-rich chloroform fraction (FRCF) of nine different citrus species was isolated by solvent fractionation technique and its effect on αglucosidase, α-amylase, glucose uptake by yeast cells and glycosylation of haemoglobin was studied. FRCF of Citrus maxima was found to show higher activity in the in vitro assays and thus it was characterized by Electrospray Ionization Mass Spectrometry (ESI-MS) analysis. This led to the identification of icariin, hesperidin and diosmetin-6,8-di-C-glucosid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The decrease in MDA levels in the treatment groups can occur due to antioxidant compounds in the R. tuberosa L. Our previous study showed that the hydroethanolic extracts of R. tuberosa L contained sorbifolin, cirsimaritin, cirsimarin, and cirsiliol-4-glucoside, which were flavonoid compounds [ 22 ]. Flavonoids have been identified to have high antioxidant activity [ 24 26 ]. The mechanism of flavonoids as antioxidants is conducted directly by donating hydrogen ions; as a result, they neutralize the effects of free radicals [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in MDA levels in the treatment groups can occur due to antioxidant compounds in the R. tuberosa L. Our previous study showed that the hydroethanolic extracts of R. tuberosa L contained sorbifolin, cirsimaritin, cirsimarin, and cirsiliol-4-glucoside, which were flavonoid compounds [ 22 ]. Flavonoids have been identified to have high antioxidant activity [ 24 26 ]. The mechanism of flavonoids as antioxidants is conducted directly by donating hydrogen ions; as a result, they neutralize the effects of free radicals [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%